Phenotypic APC Resistance in Carriers of the A20210 Prothrombin Mutation Is Associated with an Increased Risk of Venous Thrombosis - Castaman, Giancarlo; Tosetto, Alberto; Simioni, Monica; Ruggeri, Marco; Madeo, Domenico; Rodeghiero, Francesco (Thrombosis and Haemostasis, 2001)
We hypothesized that increased prothrombin levels associated with G20210A prothrombin gene mutation could affect the results of activated protein C (APC) resistance phenotype and increase the risk of venous thrombosis (VT). The increasing addition of purified prothrombin in plasma of 90 normal subjects resulted in a parallel significant increase of APC resistance. Significantly different mean n-APC-SR in 879 GG20210 subjects compared to 27 heterozygous carriers of isolated G20210A mutation was observed (1.0 ± 0.12 vs. 0.95 ± 0.11; P = 0.02) in a random sample of 906 normal population subjects. Twenty-seven families with VT and isolated G20210A mutation consecutively diagnosed during 1998-1999 were evaluated. Mean n-APC-SR was significantly lower in the 80 G20210A carriers compared to 58 GG 20210 relatives investigated, even after sex and age adjustment (0.92 ± 0.08 vs. 1.05 ± 0.13; P < 0.0001). A strong relationship between plasma prothrombin level and n-APC-SR was observed in the families. When n-APC-SR values were grouped in tertiles, the odds ratio for VTE, after exclusion of the index cases and adjustment for 20210 status, for subjects in the lowest tertile (n-APC-SR 0.73-0.90) was 4.58 (95% CI 0.78-26.88) compared to upper tertile (n-APC-SR 1.01-1.30). In conclusion, in subjects with G20210A mutation APC resistance is significantly increased, correlates with plasma prothrombin level and the carriers with the lowest APC resistance values have an increased risk of VTE.
Keywords: Venous thrombosis; FV Leiden; APC resistance; thrombophilia; prothrombin